A Systematic Review and Meta-analysis of the Effect of Multi-ingredient Preworkout Supplementation on Strength, Exercise Volume, and Anaerobic Capacity in Healthy Resistance-Trained Individuals. Issue 1 (February 2021) - Bobos, Pavlos; Nazari, Goris; Ziebart, Christina; MacDermid, Joy C.; Kostopoulos, Nikolaos
Abstract : ABSTRACT: This study assessed the effectiveness of multi-ingredient preworkout supplements (MIPSs) when compared with placebo on strength, power, exercise volume, and anaerobic capacity in healthy resistance-trained individuals. Twenty-two ( n = 22) studies and 458 participants were included. Quality of outcomes was rated as low and was downgraded mostly because of imprecision and high risk of bias. Optimal forms and strategies on MIPS consumption and use has not yet been rigorously examined. Although improvements were noted for lower body strength (repetitions) and upper body power (Watts), most results were inconclusive, and the results showing improvements were presented in low-quality studies (see Video Supplemental Digital Content 1, http://links.lww.com/SCJ/A276 ). Abstract : Supplemental Digital Content is Available in the Text.